Health-Related Quality of Life in Chronic Disorders: A Comparison across Studies Using the MOS SF-36 - Schlenk, Elizabeth A.; Erlen, Judith A.; Dunbar-Jacob, Jacqueline; McDowell, Joan; Sandra Engberg; Susan M. Sereika; Jeffrey M. Rohay; Mary Jane Bernier (Quality of life research, 1998)
The purpose of this report is to examine health-related quality of life (HRQoL) as measured by the Medical Outcomes Study Short Form-36, across patient populations with chronic disorders and to compare quality of life (QoL) in these subjects with normative data on healthy persons. Six studies, within the Center for Research in Chronic Disorders at the University of Pittsburgh School of Nursing, in patients with urinary incontinence, prostate cancer, chronic obstructive pulmonary disease (COPD), acquired immune deficiency syndrome (AIDS), fibromyalgia and hyperlipidaemia provided the data for analysis. The results demonstrated that not only did the prostate cancer and hyperlipidaemia patients have the highest QoL across the chronic disorders, but their QoL was comparable to normative data on healthy persons. Homebound, elderly, incontinent patients had the lowest QoL for physical functioning, whereas patients hospitalized with AIDS had the lowest QoL in general health and social functioning. Patients with COPD had the lowest QoL in role-physical, role-emotional and mental health. Patients with fibromyalgia had the lowest QoL in bodily pain and vitality. Compared to normative data, patients with urinary incontinence, COPD, AIDS and fibromyalgia generally had lower QoL. Prostate cancer and hyperlipidaemia patients had QoL comparable to normative data. Compared to normative data, patients with urinary incontinence, COPD, AIDS and fibromyalgia had more variability for role-emotional. AIDS patients had more variability on physical functioning, bodily pain and social functioning compared to the normative data. These data suggest that patients with various chronic disorders may have QoL that is lower in most domains compared to a healthy population. However, there may be differences in the domains affected as well as the extent of variation across specific chronic disorders.